(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
Before the readers is the fourteenth issue of Knjiženstvo, a journal for studies in literature, gender and culture, launched in 2011 as part of the research project titled Knjiženstvo - Theory and History of Womenʼs Writing in Serbian until 1915, funded by the Ministry of Education, Science and Technological Development of the Republic of Serbia. First of all, we are thrilled that this year the journal Knjiženstvo has been included in the international citation database Scopus. That is great news, as it will significantly increase the visibility and citation of our journal on a global scale. Unfortunately, like last year, we are welcoming this December 2024 with anxiety and disbelief before the “shipwreck of civilizations” that is shaking the whole world. We want to believe that the diverse contributions in this issue will be inspiring to readers and will serve as a necessary guide in the general chaos, reflecting on which direction we can (and must) think, and then act.